Design and implementation of multi-level linkage mechanism bionic pectoral fin for manta ray robot - Sun, Qixuan; Wu, Jiannan; Sheng, Chaowu; Hu, Sijie; Wang, Zhanglin; Huang, Haocai (Ocean engineering, 2023)
Manta rays achieve propulsion through the undulation of their pectoral fins, making them an important subject of study in bionics due to their efficient and agile swimming characteristics. However, currently, most biomimetic pectoral fins achieve a flapping pattern similar to that of biological fins by using multiple driving mechanisms. This paper designs an actively controlled bionic pectoral fin, driven by a single motor through a multi-level linkage mechanism, for a larger size and fully functional manta ray robot. Firstly, a bionic pectoral fin is designed based on a multi-level linkage mechanism driven by a single motor, and non-linear programming methods are innovatively applied to optimize the fin mechanism, making its motion profile more similar to the sinusoidal waveform of biological manta ray pectoral fins. Secondly, a dynamic model of the manta ray robot is established using dynamic mesh technology to verify the propulsion capability of the bionic pectoral fins and the robot's theoretical speed. Finally, prototypes of the manta ray robot are developed, and experimental research is conducted in a pool and lake. The experimental results show that the robot can complete straight-line swimming, buoyancy control, and turning in water, with a stable and flexible motion posture, proving the feasibility of this method. •A manta ray robot driven by bionic pectoral fins composed of a multi-level linkage mechanism is proposed.•Simulation of large deformation of 3D pectoral fin model using dynamic mesh technology.•The pool test confirmed that the pectoral fin can effectively realize the underwater movement of the robot.